FP2-4 Paediatric posterior fossa tumour resection rates in a small volume centre: the past decade's experience. Issue 3 (14th February 2019) - Bhatt, H; Bhatti, MI; Patel, C; Leach, P
Abstract : Objectives: Resection rates for paediatric brain tumours correlate with outcome. At the 2018 BPNG meeting a commitment to prospectively collect resection data was made. Here we review our posterior fossa resection rates for the last decade. Design: Retrospective observational cohort study of paediatric posterior fossa astrocytomas, medulloblastomas and ependymomas from 2008–2018. Primary outcome measure was extent of resection on post-op MRI, with secondary outcomes including post-op complications and need for temporary/permanent CSF diversion. Subjects: 57 patients had 62 operations for: 26 astrocytomas, 28 medulloblastomas and 8 ependymomas. Ages ranged from 7 months-16 years, with a median of 9, 7 and 6 years, respectively, and an even male: female split. Follow-up ranged from 2 months to >10 years. Methods: Patients were identified from a prospectively collected paediatric neuro-oncology database, with clinical notes and peri-operative imaging used for analysis. Our results were compared to the published literature. Results: Complete resection (CR) rates after 1 st surgery for patients with astrocytomas, medulloblastomas and ependymomas were 77%, 79% and 63%, respectively. 5/57 patients had a 2nd operation later, 3 of whom had primary CR followed by recurrence. Conclusions: Our resection rates, complications and need for CSF diversion are comparable to the literature. Factors enabling this in a low-volume centre may include a robust paediatric neuro-oncology framework, fellowship-trained subspecialty surgeons and joint operating.